Oxidized glutathione (GSSG) inhibits epithelial sodium channel activity in primary alveolar epithelial cells - Downs, Charles A. (Am J Physiol Lung Cell Mol Physiol, 2015)
Amiloride-sensitive epithelial Na(+) channels (ENaC) regulate fluid balance in the alveoli and are regulated by oxidative stress. Since glutathione (GSH) is the predominant antioxidant in the lungs, we proposed that changes in glutathione redox potential (E(h)) would alter cell signaling and have an effect on ENaC open probability (P(o)). In the present study, we used single channel patch-clamp recordings to examine the effect of oxidative stress, via direct application of glutathione disulfide (GSSG), on ENaC activity. We found a linear decrease in ENaC activity as the GSH/GSSG E(h) became less negative (n = 21; P < 0.05). Treatment of 400 μM GSSG to the cell bath significantly decreased ENaC P(o) from 0.39 ± 0.06 to 0.13 ± 0.05 (n = 8; P < 0.05). Likewise, back-filling recording electrodes with 400 μM GSSG reduced ENaC P(o) from 0.32 ± 0.08 to 0.17 ± 0.05 (n = 10; P < 0.05), thus implicating GSSG as an important regulatory factor. Biochemical assays indicated that oxidizing potentials promote S-glutathionylation of ENaC and irreversible oxidation of cysteine residues with N-ethylmaleimide blocked the effects of GSSG on ENaC P(o). Additionally, real-time imaging studies showed that GSSG impairs alveolar fluid clearance in vivo as opposed to GSH, which did not impair clearance. Taken together, these data show that glutathione E(h) is an important determinant of alveolar fluid clearance in vivo.